P03.26 Parents' and teachers' views on adolescents' sexual health to inform the development of a screening intervention for sexually transmitted infections: a qualitative study. (13th September 2015) - Wanje, GH; Masese, L; Avuvika, E; Omoni, G; Baghazal, A; McClelland, RS
Abstract : Introduction: In sub-Saharan Africa, communication between parents and adolescents regarding sex is often proscribed. Lack of parental communication could prevent adolescents from seeking sexual health services such as screening for sexually transmitted infections (STIs). We explored parents' and teachers' attitudes, and enlisted their help, in designing an STI screening intervention for female adolescents in Mombasa, Kenya. Methods: Between June 2013 and August 2014, we approached parents and teachers from three high schools. Purposive sampling was used to recruit willing parents and teachers to participate in-depth interviews (IDIs) and focus-group discussions (FGDs). Topics included general knowledge on STIs, reproductive health education, and willingness of parents to support their female adolescents in screening for STI. Transcripts were coded and analysed using content analysis. Results: We conducted 11 IDIs (5 parents and 6 teachers) and 4 FGDs (2 with parents and 2 with teachers, total of 26 participants). Most parents reported few or no discussions regarding STIs with their adolescent girls. Parents were more comfortable discussing consequences of sexual activity including loss of virginity and the potential for pregnancy. Parents tend to shift the responsibility for sexual health discourse to the teachers. The teachers, in turn, provide basic sexual and reproductive health education including abstinence, overview of STIs, and understanding of puberty, according to the educational curriculum. Both parents and teachers found the idea of screening for STIs in female adolescents to be acceptable, and were comfortable with our contacting them through informational meetings at schools. However, all parents felt that adolescents' screening results should be shared with their parents. Conclusion: Parents and teachers were supportive of a STI screening intervention, beginning with informational meetings at schools. Research and programs that aim to provide STI screening for adolescents in this setting must address the issue of whether results will be disclosed to parents. Disclosure of interest statement: This study was supported by the University of Washington Global Centre for Integrated Health of Women, Adolescents, and Children. Infrastructure and logistical support for the Mombasa Field Site was received from the University of Washington and Fred Hutchinson Cancer Research Centre's Centre for AIDS Research (grant number P30-AI27757). No pharmaceutical grants were received in the development of this study.